Analisis Kontribusi Persepsi Pendekatan Pembelajaran dan Efikasi Diri terhadap Capaian Prestasi Belajar Matematika - Sri Suyamti (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study was prompted by the declining mathematics achievement of Indonesian students in international assessments (PISA/TIMSS), which stems from both cognitive and psychological barriers. The research aims to analyze the contribution of students' perceptions of teaching approaches and self-efficacy as an integrative solution to improve academic outcomes. Methods – This quantitative study employed a correlational survey method involving 86 eighth-grade students from three State Madrasah Tsanawiyah (MTs) in South Jakarta, selected via simple random sampling. Data was collected using Likert-scale questionnaires for perception and self-efficacy variables, while mathematics achievement was measured through students' learning outcomes. Data analysis was performed using multiple linear regression via SPSS 22.0. Findings – The findings confirm that perceptions of teaching approaches and self-efficacy simultaneously contribute significantly (77.2%) to mathematics learning achievement Fobs = 140.699 Sig. = 0.000. Partially, the perception of teaching approaches serves as a more dominant predictor tobs = 6.368 compared to self-efficacy tobs = 4.416. This proves that students' positive interpretation of teaching strategies and their belief in their own capacity are robust predictors of academic success.Research Implications – These findings imply that educators must adopt adaptive teaching strategies that foster a growth mindset and mental resilience.